Perencanaan Pembangunan Tempat Pengolahan Sampah Terpadu: (Studi Kasus Pulau Kaledupa, Kabupaten Wakatobi, Provinsi Sulawesi Tenggara) - Mubaraq S., Arya Fadh; Ndibale, Wa; Rosdiana, Rosdiana (Universitas Muhammadiyah Kendari, 2025)
The increasing volume of waste generation on Kaledupa Island, Wakatobi Regency, which reaches 14.5 tons per day with an estimate of 0.6625 kg/capita/day, requires an integrated and environmentally friendly waste management system. To meet this need, it is planned to build an Integrated Waste Processing Site (TPST) on an area of ​​15,000 m² in South Balasuna Village. The methods used include land capacity analysis based on waste generation volume and TPST analysis. The results of this study indicate that with the assumption of an effective area of ​​12,000 m², TPST Kaledupa can operate for more than 10 years without the need for additional land expansion. The designed system includes 17 work areas and 1 Green Open Space (RTH) area, starting from the waste drop-off point to shredding, drying, and final storage. In addition, environmental handling systems such as leachate processing, gas ventilation, and odor control are also prepared to minimize negative impacts. It is hoped that this TPST will be able to become a model for integrated waste management that is efficient, safe and sustainable in the island region